Extended TAM Theory with Perceived Risk and Social Influence to Measure Consumer's Intention to use E-Wallet in Indonesia - Shofiyyah K. Nisa; K Kussudyarsana; Ihwan Susila; S Soepatini (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study seeks to comparatively examine the differences in consumers' intentions to use e-Wallets in Indonesia by employing an extended Technology Acceptance Model (TAM). The traditional TAM framework is expanded by incorporating two additional constructs: perceived risk and social influence. The research utilized an online survey involving 320 Indonesian respondents who had used an e-Wallet at least once within the past three months. The collected data were analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach using Smart-PLS software. The results offer both theoretical and practical insights, revealing that perceived ease of use has a significant impact on perceived usefulness in the context of e-Wallet adoption. Therefore, digital payment providers should focus on enhancing perceived usefulness to promote greater user acceptance. To the best of the authors' knowledge, this study is among the first to explore this topic and provides valuable directions for future research. By comparing consumer behavior between independent and embedded e-Wallet users, three key differences are identified. The findings are expected to assist digital payment providers in managing and improving e-Wallet systems and platforms more effectively, thereby supporting the design and implementation of services that achieve stronger consumer acceptance.